Transcription of Nonrepeated DNA in Neonatal and Fetal Mice - Gelderman, A. H. (1971)
The transcription of nonrepeated DNA sequences was measured by hybridization of RNA from neonatal and fetal mice to mouse DNA using three different techniques. The measurements indicate that a large part (about 70%) of the rapidly-labeled fetal RNA is transcribed from nonrepeated DNA sequences. It appears that more than 12% of the single-copy DNA sequences are represented in the RNA of newborn mice.